(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Toni Morrison, Maya Angelou, Paul Marshall, Alice Walker, and Gloria Naylor were among the American writers who saw writing as a way to break free, a strategy for rebellion, and a creative way to express oneself. She follows in Edward Said’s footsteps by exploring how the dominant group manipulates black reality to serve its own agenda; Said revealed orientalism as a Western tactic for moulding and dominating the Orient. Her current projects include an Afro-centric perspective and an African-American poetics. While exploring the intricacies of black women’s life in white America, she tries to comprehend the contradiction of her African-American identity. This presentation will examine Toni Morrison’s works through the lens of literary criticism.